2018
DOI: 10.1111/birt.12384
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic childbirth and active management of the third stage of labor: A latent class model of risk for postpartum hemorrhage

Abstract: AMTSL may not be as beneficial to women undergoing physiologic birth. Further study of the etiology of PPH in these women is indicated to inform preventive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Women who receive oxytocin during labor augmentation are known to require greater quantities of oxytocin prophylaxis during the third stage of labor than women whose labors are not augmented (Belghiti et al, 2011;Foley et al, 2018;Lavoie et al, 2015). Moreover, women who do not receive oxytocin during labor (physiologic birth) may not appreciate the same benefits of postpartum prophylactic oxytocin for minimizing PPH compared to women with oxytocin infusion in labor (Davis et al, 2012;Erickson et al, 2017Erickson et al, , 2019Kearney et al, 2018). Thus, oxytocin exposure during labor appears to influence the occurrence of PPH and the efficacy of oxytocin prophylaxis in the third stage of labor.…”
Section: Discussionmentioning
confidence: 99%
“…Women who receive oxytocin during labor augmentation are known to require greater quantities of oxytocin prophylaxis during the third stage of labor than women whose labors are not augmented (Belghiti et al, 2011;Foley et al, 2018;Lavoie et al, 2015). Moreover, women who do not receive oxytocin during labor (physiologic birth) may not appreciate the same benefits of postpartum prophylactic oxytocin for minimizing PPH compared to women with oxytocin infusion in labor (Davis et al, 2012;Erickson et al, 2017Erickson et al, , 2019Kearney et al, 2018). Thus, oxytocin exposure during labor appears to influence the occurrence of PPH and the efficacy of oxytocin prophylaxis in the third stage of labor.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have found prophylactic oxytocin/active management is associated with higher PPH rates 17,18,28,29 ; however, most of the births in these studies were not community births. Indeed, our regression modeling also shows that preventive pharmaceutical use was associated with higher odds for PPH when controlling for state, midwife credentials, parity, hemorrhage/cesarean history, and birth setting—however, we must interpret these findings with caution given that the timing of the administered medication was not recorded and it may not represent “active management” as currently defined.…”
Section: Discussionmentioning
confidence: 92%
“…The second study utilized the robust clinical dataset being gathered by the nurse-midwifery practice at Oregon Health and Science University on all births from 2012 [ 32 ]. I had recently been introduced to the latent mixture (latent class) analytic approach and felt it was highly relevant to the study of childbirth.…”
Section: Dot-to-dot: Oxytocin Function From Labor To Postpartummentioning
confidence: 99%